A double Descemet’s stripping endothelial keratoplasty on a penetrating keratoplasty - Goh, Li Yen (BMJ Case Rep, 2017)
A patient with keratoconus underwent a penetrating keratoplasty (PK) in his right eye. This failed after 12 years following phacoemulsification surgery. A Descemet's stripping endothelial keratoplasty (DSEK) was carried out which failed and detached after 4 months. Subsequently, a second DSEK was performed which failed after 2 months but remained attached. This graft was retained in the cornea and a third DSEK button was placed without removing the failed DSEK graft. The cornea cleared well and patient’s vision was 6/9 at 18 months postsurgery. Optical coherence tomography showed the two DSEK grafts closely applied to each other and to the recipient cornea. Stripping a failed DSEK graft performed for a previous failed PK carries the risk of internal dehiscence of the PK graft–host junction. This was avoided by placing the second DSEK graft on the failed previous DSEK graft with good visual outcome indicating that this option can be clinically considered.